Healing Roots: An Ayurvedic Approach to Disease Management in Charmadal – A Case Study - Sahu, Kalpana; Yadav, C R; Prakash Gurao, Rashmi (International Research Journal of Ayurveda & Yoga, 2025)
Charmadal is classified under Kshudra Kushtha in Ayurvedic texts and is characterized by Raga, Kandu, Pidaka, Ruja, Tvacha chhidra, and Sparsha Asahyata. The clinical presentation of Dyshidrotic Eczema shows a striking resemblance to Charmadal as described in the Samhitas. According to Charaka Samhita, Charmadal is one of the types of Kshudra Kushtha (minor skin disorders). It is predominantly a Pitta-Kapha dosha condition. Modern medical management offers only temporary relief with topical corticosteroids, which are palliative in nature. However, Ayurvedic Chikitsa Sutra for Charmadal includes both Shodhana (purificatory therapies) and Shamana (palliative treatment), as detailed in the classical texts. The administration of appropriate Shamana Aushadhis (oral Ayurvedic medicines) led to significant symptomatic relief, reduction in lesion severity, and notable enhancement in the patient’s overall Jeevana Guna (quality of life. At the National Institute of Ayurveda in Jaipur, a 29-year-old woman came to the Kriya Sharir outpatient department complaining of reddish-blackish skin lesions on her arms, legs, face, abdomen, and neck area. She also complained of intense itching, burning, watery discharge, and blood leaking from the lesions after scratching for 3 years. The patient’s symptoms were completely eliminated after a 3-month course of treatment that included both external and internal Ayurvedic drugs. The results of this case study demonstrate that Ayurvedic medications can effectively treat this illness with no discernible adverse effects.